2017
DOI: 10.1017/s1751731116002378
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and castration on the growth rate, blood lipid profile, liver histology and feed conversion in Green-legged Partridge cockerels and capons

Abstract: The surgical castration of male chickens induces hormonal changes, which permanently influence metabolic processes in birds. The aim of this study was to determine the effect of age and castration on the growth rate, feed conversion, lipid profile and histopathological changes in the livers of cockerels and capons. The experimental materials comprised male chickens of the Green-legged Partridge breed (old traditional Polish chicken breed), raised to 28 weeks of age. At 8 weeks of age, 100 birds were castrated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
5
10
1
3
Order By: Relevance
“…The assessed groups of birds differed in terms of the internal organ share, and the greatest effect was exerted by the liver and gizzard share, which was significantly higher in sterilized birds. This corresponds to the results obtained by Rahman et al (2004), Chen et al (2006Chen et al ( , 2007, Zawadzka et al (2017) and Murawska et al (2019). The authors indicate that the liver is the main site of fatty acids synthesis in birds, and the increase in its mass may be caused by increased lipogenesis processes.…”
Section: Discussionsupporting
confidence: 90%
“…The assessed groups of birds differed in terms of the internal organ share, and the greatest effect was exerted by the liver and gizzard share, which was significantly higher in sterilized birds. This corresponds to the results obtained by Rahman et al (2004), Chen et al (2006Chen et al ( , 2007, Zawadzka et al (2017) and Murawska et al (2019). The authors indicate that the liver is the main site of fatty acids synthesis in birds, and the increase in its mass may be caused by increased lipogenesis processes.…”
Section: Discussionsupporting
confidence: 90%
“…Caponization is carried out to produce meat with exceptional flavor (Díaz et al, 2010; Calik et al, 2015; Adamski et al, 2016; Amorim et al, 2016). Previous research revealed increased deposition of fat in caponized birds, in particular abdominal fat and mesenteric fat, which can decrease carcass dressing percentage (Zawacka et al, 2017). On the other hand, the accumulation of lipids in the muscle tissue of capons improves the palatability of meat (Amorim et al, 2016; Gesek et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, consumption leveled off in subsequent weeks, being similar to that of the other experimental groups. On the other hand, these differences in consumption due to the effect of castration have not been observed 4,20,22,23 . This variability in food consumption is probably due to various factors, including the genetic line and the place of origin of the chickens 4,17,25 .…”
Section: Figure 1 Percentages For the Mortality Variablementioning
confidence: 90%